High mortality in obese women diabetics with acute myocardial infarction. Issue 6077 (25th June 1977) - Tansey, M J; Opie, L H; Kennelly, B M
Abstract : The factors associated with mortality in 89 diabetics and 793 non-diabetics with acute myocardial infarction who were initially admitted to a coronary care unit were analysed retrospectively. During their stay in hospital diabetics had twice the mortality of non-diabetics. The higher mortality among diabetics was largely accounted for by obese women, who had a hospital mortality of 43%. There was an increased incidence of congestive heart failure in such patients. A therapeutic trial should be performed in such patients to assess whether insulin has an effect on infarct size.